Geostatistics Toronto 2021 Quantitative Geology and Geostatistics - Avalos Sotomayor, Sebastian Alejandro; Ortiz, Julian M.; Srivastava, R. Mohan (Springer Proceedings in Earth and Environmental Sciences, 2023)
This open access book provides state-of-the-art theory and application in geostatistics. Geostatistics Toronto 2021 includes 28 short abstracts, 18 extended abstracts, and 7 full articles in the fields of geostatistical theory, multi-point statistics, earth sciences, mining, optimal drilling, domains, seismic, classification uncertainty risk, and artificial intelligence and machine learning. All contributions were presented at the 11th International Geostatistics Congress held in virtually at Toronto, Canada, from July 12-16, 2021. This book is valuable to researchers, scientists, and practitioners in geology, mining, petroleum, geometallurgy, mathematics, and statistics.